COMPARATIVE ANALYSIS : WORKING CAPITAL EFFICIENCY MANUFACTURING COMPANIES LISTED ON INDONESIAN STOCK EXCHANGE - Nurlaela Nurlaela (International Journal of Economics Management and Social Science, 2018)
This study aims to determine which companies are more efficient use of working capital between PT. Mayora Indah Tbk. and PT. Siantar Top Tbk. Method analysis is descriptive with the analysis of financial ratios used are the ratio of activities of asset turnover, inventory turnover, and working capital turnover. Results of research that PT. Mayora Indah Tbk. activity ratio of the asset turnover is 6.59 times, inventory turnover is 23.87 times, and the working capital turnover is 18.07 times and PT. Siantar Top Tbk. asset turnover ratio of 5.9 times, inventory turnover 27.78 times, and turnover of working capital -910.71 times. Both companies are then PT. Mayora Indah Tbk. more efficient use of working capital than PT. Siantar Top Tbk. which is listed on the Indonesia Stock Exchange.